Psychosocial aspects of choosing a couple partner - Calin, Mariana Floricica; Sandu, Mihaela Luminita (Technium Social Sciences Journal, 2021)
We often meet in couple relationships imaginary or real people who are found between the two partners and who leave a significant influence on the evolution and quality of the couple's relationship. This aspect has been addressed by specialists in socio-psychology, who have looked at how couples who establish an ideal in their current or future partners are affected, so that now these studies have become theoretical information that brings a clarification on the ideals and idealization in couple relationships. Thus, several theories have been crystallized that explain these phenomenon.